Religion and Governance: Examining the Intersection in Contemporary Politics - Gangopadhyay, Mayurakshee (Religion and Policy Journal, 2023)
Research Problem: This study investigates the intricate relationship between religion and governance within contemporary politics. It aims to understand how religion influences and is influenced by the structures and practices of governance in today's world, considering historical perspectives, empirical data, and case studies from various regions. Research Purposes: The primary purpose of this study is to provide a comprehensive understanding of the impact of religion on governance and its implications for society. It seeks to uncover the complex dynamics, challenges, and opportunities that arise when religious beliefs intersect with political authority and decision-making mechanisms. Research Methods: Methodologically, this study employs a multidisciplinary approach, integrating qualitative and quantitative methods. It utilizes content analysis, interviews, surveys, and comparative analysis to explore the multifaceted ways in which religion influences governance within contemporary politics. Results and Discussion: The study delves into the multifaceted ways in which religion influences and is influenced by governance structures and practices in contemporary politics. It discusses the complex dynamics, challenges, and opportunities that arise when religious beliefs intersect with political authority and decision-making mechanisms. Research Implications and Contributions: This study underscores the importance of thoughtful consideration and dialogue in shaping inclusive and effective political systems that accommodate religious diversity while upholding fundamental principles of governance. By providing insights into the impact of religion on governance and its implications for society, this study contributes to ongoing discourse and research in this field.